Perspektif Leadership Agility dalam Penetapan POKIR (Studi pada DPRD Kabupaten Banjar) - De Nisa, Gina; Santoso Haryono , Bambang; Putra , Fadillah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Indonesia adheres to a decentralized system, which means that each region has the right and authority to regulate its own region, for this reason it needs a leader who can protect its region in order to achieve development goals. There is a need for cooperation between the community and the government to achieve this goal. One of the government's efforts to increase development is through Principles of Thought (Pokir). This research aims to explain the influence of leadership on increasing development in Banjar district through the existence of the DPRD's Pokir. This research uses a quantitative approach with a descriptive research type by distributing questionnaires to the public using purposive sampling techniques to 370 samples. The results of this research are that Leadership agility influences Pokir in improving development in Banjar district. Context-Setting Agility, Creative Agility, and Self-leadership Agility variables have a positive and significant effect on the creation of leadership agility in Banjar Regency, while creative agility has a negative and significant effect on Leadership Agility.